2015
DOI: 10.1002/chem.201503104
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering a 20‐Year‐Old Conundrum: The Mechanisms of Reduction by the Water/Amine/SmI2 Mixture

Abstract: The reaction of SmI2 with the substrates 3-methyl-2-butanone, benzyl chloride, p-cyanobenzyl chloride, and anthracene were studied in the presence of water and an amine. In all cases, the water content versus rate profile shows a maximum at around 0.2 M H2 O. The rate versus amine content profile shows in all cases, except for benzyl chloride, saturation behavior, which is typical of a change in the identity of the rate-determining step. The mechanism that is in agreement with the observed data is that electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…Since water is known to be a good complexing agent to SmI 2 and may compete with the ligands attached to the benzene ring, we have optimized the reaction conditions for BNO and found that the maximum yield is obtained with 0.2 M of water, similar to the value previously found for the water/amine/SmI 2 reactions . Thus, under these conditions, the binding of SmI 2 to BNO is not hampered by the presence of water at this concentration.…”
Section: Figuresupporting
confidence: 73%
See 1 more Smart Citation
“…Since water is known to be a good complexing agent to SmI 2 and may compete with the ligands attached to the benzene ring, we have optimized the reaction conditions for BNO and found that the maximum yield is obtained with 0.2 M of water, similar to the value previously found for the water/amine/SmI 2 reactions . Thus, under these conditions, the binding of SmI 2 to BNO is not hampered by the presence of water at this concentration.…”
Section: Figuresupporting
confidence: 73%
“…We showed that, under these conditions, the rate of the back electron transfer is significantly slowed down by deprotonating a water molecule attached to the Sm +3 . This generation of a hydroxide anion attached to the Sm +3 reduces the effective charge on the samarium and significantly decreases its ability to pull the electron back from the radical anion . As a result, the forward reaction is considerably enhanced.…”
Section: Figurementioning
confidence: 99%
“…UV/Visible spectra study in the presence of Et 3 N (0.05 M–0.5 m ) shows no change in the shape of SmI 2 spectrum (Figure S12). It known that under similar condition, water significantly changes the shape of SmI 2 spectrum . The enthalpy of complexation for water and Et 3 N measured through ITC experiments was found to be comparable (−2.5 kcal mol −1 for water and −3.3 kcal mol −1 for Et 3 N).…”
Section: Resultsmentioning
confidence: 88%
“…Rate of reactions were monitored by following the disappearance of the SmI 2 -additive complex absorbance. Reduction of anthracene, 3-methyl-2-butanone, and cyclohexanone resulted in 9,10-dihydroanthracene, 3-methyl-2-butanol, and cyclohexanol, respectively. The reduction of benzyl chloride provided a mixture of toluene and 1,2-diphenylethane …”
Section: Methodsmentioning
confidence: 99%